Lipid nanodomains change ion channel function. Issue 35 (31st August 2017) - Weinrich, Michael; Worcester, David L.; Bezrukov, Sergey M.
Abstract : Two distinct lifetimes are observed for gramicidin channels in model lipid raft membranes exhibiting lateral domain separation at the nanoscale. Abstract : Signaling proteins and neurotransmitter receptors often associate with saturated chain and cholesterol-rich domains of cell membranes, also known as lipid rafts. The saturated chains and high cholesterol environment in lipid rafts can modulate protein function, but evidence for such modulation of ion channel function in lipid rafts is lacking. Here, using raft-forming model membrane systems containing cholesterol, we show that lipid lateral phase separation at the nanoscale level directly affects the dissociation kinetics of the gramicidin dimer, a model ion channel.